Raw milk quality in Northwestern Colombia - Jiménez Suárez, Gustavo; Villegas Pomarez, José; Calderón Rangel, Alfonso; Rodríguez Rodríguez, Virginia; Maza Angulo, Libardo; Vergara Garay, Oscar (Revista Colombiana de Ciencias Pecuarias, 2016)
the worldwide trend in agro industries is to optimize food quality and obtain safe products for human consumption. It is important to produce milk with excellent physicochemical and microbiological quality to reduce public health risks. Objective: to evaluate the physicochemical and microbiological quality of milk and udder health in northwest Colombia, through the raw milk received at a leading dairy plant in Valledupar (Colombia). Methods: a non-probability sampling and a cross-sectional study were conducted. Raw milk samples from 186 beef and milk (dual purpose) farms were collected. Physicochemical parameters, mesophilic and somatic cell counts were determined. Data were analyzed by descriptive statistics using SAS software. Results: physicochemical parameters were within the normal range in accordance with Colombian Decree No. 616 of 2006. The average mesophilic and somatic cell count was 305,279 colony forming units (CFU)/mL, and 523,207 somatic cells (SC)/mL, respectively. Sixty-eight percent of the farms had somatic cell counts greater than 200,000 SC/mL, which is the threshold for bovine mastitis. Conclusion: physicochemical quality of milk was good, but there were shortcomings in microbiological quality and udder health. Therefore, efforts are required to prevent this problems and to implement excellent management practices in the farms.